Modeliranje gorivnih celic - Dujc, Jaka (Gradbeni vestnik, 2018)
The main topics of this article are numerical models of PEM fuel cells. It is estimated that PEM fuel cells will play a leading role in the pursuit of cleaner technologies in mobility and in stationary applications. Multi-scale modeling of PEM fuel cells gives us insight into complex physical and electro-chemical processes and also serves as a tool for optimizing components and materials. We present the typical approaches used in the simulations and analyses of microstructures, membrane-electrode-assembly and smaller-size fuel cells. In more detail we consider the 2 + 1D approach for the analysis of large fuel cells. In this approach, the fuel cell is divided into regions of 2D and 1D domains. Two parallel 2D domains represent the anode and cathode side flow fields and gas diffusion layers. Anode and cathode sides are connected by the 1D domains, representing the membrane electrode assembly.
Keywords: coupled problems; finite element method; metoda končnih elementov; mobility; mobilnost; numerical models; numerični modeli; PEM gorivne celice; polymer electrolyte membrane fuel cells; povezani problemi; simulacije; simulation; steel structures